Modern Information Technologies And Political Communication In The Activities Of Law Enforcement Agencies (Eurasian Journal of Media and Communications, 2025)
This research article analyzes the improvement of the socio-legal system based on the concept of political communication. In this regard, it examines the activities of law enforcement agencies and public associations, as well as factors for harmonizing their activities